Efeito da radiação ultravioleta e da névoa salina na resistência ao riscamento de polietilenos usados em rolos de carga de transportadores de correia - Kouketsu, Fernanda (2021)
The conveyor belts consist of many parts, among them the idler rollers, which aims to support and guide the belt movement towards a specified direction. Usually made from steel tubes that can weight up to 70Kg, currently there are carrying idlers made from polymeric tubes, which are lighter, but, as well as the metallics, they are subject to the weather-conditions, such as UV radiation and humidity, as well as the abrasive wear. This work intends to evaluate the influence of the exposure to weatherconditions on the scratch resistance of four polyolefin used in commercial idler rollers: high-density polyethylene filled with carbon black (HDPE + 2-3% CB) (two different suppliers), high-density polyethylene filled with glass fiber (HDPE + 75% GF) and the ultra-high molecular weight polyethylene (UHMWPE). For this purpose, these materials were analyzed under the original supplied condition, after artificial UV radiation aging and after salt spray exposure. An idler was also analyzed after 9 months of field work (HDPE + 2-3% CB). Were performed tensile tests, thermogravimetric analysis (TGA), Differential Scanning Calorimetry (DSC), DynamicMechanical Analysis (DMA), Fourier-transform infrared spectroscopy (FTIR), hardness and relative density tests in order to evaluate the characteristics of each material. The scratch tests were carried out with a steady load of 5N, velocity of 0.17mm/s and a hardened metal cutting tool. The scratching measurement by rugosimeter 2D, scanning white light interferometry (SWLI) and the scanning electron microscopy (SEM) analysis were performed after the scratch tests, in order to identify and evaluate the wear mechanisms. The results indicated that the exposure to weather-conditions affected the tribological behavior of the materials, mainly after UV radiation exposure, particularly for the UHMWPE (which doesn’t possess additives for UV protection or reinforcement material), elevating the apparent friction coefficient and weakening the surface. The wear micro-mechanism identified for this material was micro-craking. For the other materials, micro-ploughing and micro-cutting were the predominant wear mechanisms.